The role of Information and Communication Technology (ICT) in Transforming Education: Trends, Applications, and Impacts (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Information and Communication Technology (ICT) has become a cornerstone of modern education, significantly transforming teaching, learning, administration, and content delivery. This paper explores the evolution, integration, and impact of ICT across various levels of education, with special attention to its application in Indian institutions. It highlights the paradigm shift in pedagogy driven by ICT tools such as multimedia content, digital classrooms, online platforms, and e-learning modules. Government-led initiatives like SAKSHAT and RMSA demonstrate India's growing commitment to digital literacy and inclusive education. The paper also discusses the critical role of ICT in empowering educators, bridging the digital divide, enhancing evaluation practices, and increasing students’ engagement and academic performance. Ultimately, ICT is not just a support mechanism but a driver of educational innovation and equity in the 21st century.